KETIMPANGAN HUBUNGAN INDONESIA-MESIR 1950-2010: KAJIAN TENTANG TEORI RESIPROSITAS - Abdurrahman Mohammad Fachir, Irwan Abdullah, Sangidu, Siti Mutiah Setiawati (Arabic Literature Department, 2014)
Egypt was the first country in the world that recognized the independence of Indonesia. Egypt is also the first country signing a friendship agreement with Indonesia,which was followed by the opening of representative offices in Cairo and in Jakarta in1950/1951. More than that, Egypt is the country where Indonesia children studying sincebefore the 19th century to the present. Historical and emotional Indonesia-Egypt relationsshould be an important asset for both countries to improve more strategic relations andcooperation, so it becomes more meaningful each other. However, the opposite happened.Indonesia has always looked at the importance of Egypt, but Egypt only one eye seesIndonesia. Unequal, unbalanced and biased relationship reflected from two things,namely the formation of representatives and officials visit the country. This dissertation research aims to answer the question why the relationshipbetween Indonesia and Egypt from 1950 to 2010 is unequal, unbalanced and biased, andwhat efforts are offered to improve the relationship between Indonesia and Egypt so thatIndonesia has interesting bargaining power, so that Indonesia is considered important byEgypt. Hopefully, this research has benefits for the development of InternationalRelations and Middle East Studies as well as to provide input to the Government ofIndonesia in making decision related to foreign policy towards Egypt and generate thebasis for the implementation of Indonesia's foreign relations in the future, especiallybetween Indonesia and Egypt.